Molecular Detection of Per-1 Type Extended Spectrum Β-Lactamase among Clinical Isolates of Klebsiella Pneumoniae in Baghdad Hospitals - Buthainah Mohammed Taha (Journal of Global Pharma Technology, 2017)
This study was aimed to determine the presence of PER-1 type Extended-Spectrum β-Lactamases (ESBLs) in clinical isolates of Klebsiella pneumonia in Baghdad. During a period extended for three months ((July- September, 2014), 26 clinical K. pneumoniae isolates were collected from two hospitals in Baghdad (Fattima-AL-Zahra hospital for pediatric and obstetric and Baghdad Teaching Hospital). Out of these 26 isolates, 11 isolates from blood, 7 from urine, 6 from sputum and 2 from wound. All isolates had 100% resistance to ampicillin and cefazolin while the most effective antibiotics were imipenem and meropenem with high sensitivity rate (92.31%). Out of 26 K. pneumoniae isolates, 17(65.38%) isolates were positive ESBL producing isolates phenotypes and 9(34.62%) isolates were negative ESBL producing isolates (non ESBLs) .Genotypic Detection of blaPER-1 gene by polymerase chain reaction showed that out of all seventeen ESBL-producing K. Pneumoniae isolates by phenotypic detection, 6 isolates (13.8%) were contained blaPER-1 gene (925bp).Keywords: Klebsiella pneumonia, Blaper-1 gene, Extended-spectrum β -lactamases (ESBLs).